2006
DOI: 10.1111/j.1075-122x.2006.00199.x
|View full text |Cite
|
Sign up to set email alerts
|

Breast Cancer in Limited-Resource Countries: An Overview of the Breast Health Global Initiative 2005 Guidelines

Abstract: Breast cancer is the most common cause of cancer-related death among women worldwide, with case fatality rates highest in low-resource countries. Despite significant scientific advances in its management, most of the world faces resource constraints that limit the capacity to improve early detection, diagnosis, and treatment of the disease. The Breast Health Global Initiative (BHGI) strives to develop evidence-based, economically feasible, and culturally appropriate guidelines that can be used in nations with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
259
1
9

Year Published

2007
2007
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 294 publications
(270 citation statements)
references
References 23 publications
1
259
1
9
Order By: Relevance
“…27 No obstante, requiere un esfuerzo multisectorial permanente, con mejor planeación y distribución de los recursos existentes. Éste es un esfuerzo impostergable.…”
Section: Discussionunclassified
“…27 No obstante, requiere un esfuerzo multisectorial permanente, con mejor planeación y distribución de los recursos existentes. Éste es un esfuerzo impostergable.…”
Section: Discussionunclassified
“…Thus results from an outsourced trial traveled back to shape US policies and practices, which, in turn, led many international health agencies to call for the universal adoption of more expensive screening modalities like mammography in place of other techniques like BSE. Ironically, Jemal and colleagues (2011:74) reported that about half the new breast cancer cases and 60% of the deaths are estimated to occur in economically developing countries, yet early detection through mammography is cost prohibitive and not feasible in most of them (Anderson, Shyyan, Eniu, et al 2005). Instead, Anderson and colleagues (2008) recommended that early detection strategies in these areas include the promotion of awareness of early signs and symptoms (exactly what BSE was originally supposed to do) and screening by clinical breast examination.…”
Section: Cancer Is a Transnational Phenomenonmentioning
confidence: 99%
“…In fact, in most developing countries, determination of hormone receptor status is not a part of standard protocol for treatment of breast cancer, despite the fact that the Breast Health Global Initiative (BHGI) classified hormone receptor status determination as a basic level therapy in the treatment of breast cancer. 15,16 India is one such developing country, where breast cancer is the most common cancer among women in most places, mainly in the urban areas. 17 Despite this, there have been very few studies on breast cancer in India.…”
Section: Uiccmentioning
confidence: 99%